EXPERIMENTAL STUDY ON ANTI-FREEZING ADHESIVE TURNABOUT ROLLER - WANG ChunHua; QU Hui; XU HanWen; WANG ZhongXian (Jixie qiangdu)
According to the freezing adhesion problem which exists between the coal and the belt conveyor turnabout roller surface,the freezing adhesive strength test device is created. To simulate the belt conveyor turnabout roller surface environment,- 30℃ temperature and 3h freezing time of stress conditions,several different materials are studied with moisture content 30% of the coal slime,each of the freezing adhesive characteristic. Comparative tests have proved that UHMW-PE material in normal,tangential freezing adhesive strength is lower than test of other materials,which proves that it is provided with good anti-freezing adhesive capability. According to UHMW-PE package roller based on the actual application situation can further illustrate that the UHMW-PE can be used as roller coating in order to achieve anti-freezing adhesive effect.